From novice to expert: preparing your peer review - Diana M. Proctor; Rachy Abraham; Shannon Esher Righi (mBio, 2025)
ABSTRACT Peer review is the process by which the quality of scholarly work is assessed prior to being published, presented, or funded. The consequences of flawed research entering the public domain in the “post-truth” era highlight the need to improve peer review quality, which we believe can be achieved by standardizing training. Here, we aim to enhance the quality of published literature by presenting a systematic guide to train new reviewers (and aid experienced ones) in the art of peer reviewing the rigor of scientific manuscripts.